Millimeter‐Wave Digital Coding Metasurfaces Based on Nematic Liquid Crystals. Issue 12 (9th September 2019) - Wang, Qiang; Zhang, Xin Ge; Tian, Han Wei; Jiang, Wei Xiang; Bao, Di; Jiang, Hao Lin; Luo, Zhang Jie; Wu, Li Ting; Cui, Tie Jun
Abstract: Metasurfaces provide an unprecedented capability in manipulating electromagnetic waves. In this work, a millimeter‐wave (mmW) digital coding metasurface based on nematic liquid crystals (NLCs) is proposed and realized. By tuning the bias voltage loaded on the NLCs, the effective permittivity of the NLCs substrate is changed, thus providing different reflection phases. As a proof of concept, mmW beam splitting and mmW beam steering at mmW frequencies are demonstrated using a single metasurface platform. The experimental results are in good agreement with numerical simulations. The proposed digital coding metasurfaces have promising applications on planar mmW devices, such as multi‐beam antennas, beam‐scanning antennas, and wave controllers. Abstract : A millimeter‐wave (mmW) digital coding metasurface based on nematic liquid crystals (NLCs) is proposed and realized. As a proof of concept, beam splitting and beam steering at mmW frequencies are demonstrated using a single metasurface platform. The proposed digital coding metasurfaces have promising applications on planar mmW devices, such as multi‐beam antennas, beam‐scanning antennas, and wave controllers.